2020
DOI: 10.1002/lio2.446
|View full text |Cite
|
Sign up to set email alerts
|

The clinical consequences of the COVID‐19 lockdown: A report from an Italian referral ENT department

Abstract: Objectives: To evaluate the clinical effects of health care reorganization because of COVID-19, in a non-red zone Italian referral department of Otorhinolaryngology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
1
14
1
1
Order By: Relevance
“…The main result of our study was that total ER admissions in 2020 decreased by 81%. Our results are similar to previous studies that have demonstrated the same trend in both child and adult patients [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. We can speculate that social-distancing measures, the use of face masks, hand washing, and the complete closure of social activities may have contributed not only to the reduction of SARS-CoV-2 diffusion [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] but also to the reduction of the spread of other diseases, particularly of acute communicable diseases, as confirmed in a recent study [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…The main result of our study was that total ER admissions in 2020 decreased by 81%. Our results are similar to previous studies that have demonstrated the same trend in both child and adult patients [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. We can speculate that social-distancing measures, the use of face masks, hand washing, and the complete closure of social activities may have contributed not only to the reduction of SARS-CoV-2 diffusion [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] but also to the reduction of the spread of other diseases, particularly of acute communicable diseases, as confirmed in a recent study [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…Total laryngectomy and cT4aN0 was performed on the patients. Outpatient ENT consultations and treatments of choice decreased by 78% and 75%, respectively, while emergency surgery increased by 128% during this epidemic [12] .…”
Section: Discussionmentioning
confidence: 99%
“…As others have described, the COVID-19 pandemic has resulted in significant reductions in the overall volume of procedures and outpatient consultations in otolaryngology [ 2 , 19 ] and in delays in the care of non-COVID-19 otolaryngologic pathologies [ 20 ]. Some groups have reported reductions in inpatient and emergency room otolaryngologic consultations in Europe [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%